Matrix stiffness modulates the activity of MMP-9 and TIMP-1 in hepatic stellate cells to perpetuate fibrosis - Lachowski,D; Cortes,E; Rice,A; Pinato,D; Rombouts,K; Del,Rio Hernandez A (Scientific Reports, 2019)
Liver fibrosis is characterised by a dense and highly cross-linked extracellular matrix (ECM) which promotes progression of diseases such as hepatocellular carcinoma. The fibrotic microenvironment is characterised by an increased stiffness, with rigidity associated with disease progression. External stiffness is known to promote hepatic stellate cell (HSC) activation through mechanotransduction, leading to increased secretion of ECM components. HSCs are key effector cells which maintain the composition of the ECM in health and disease, not only by regulating secretion of ECM proteins such as collagen, but also ECM-degrading enzymes called matrix metalloproteinases (MMPs) and their inhibitors (TIMPs). Uninhibited MMPs degrade ECM proteins to reduce external rigidity. Using fibronectin-coated polyacrylamide gels to alter substrate rigidity without altering ligand density, we show that fibrotic rigidities downregulate MMP-9 expression and secretion, and also upregulate secretion of TIMP-1, though not its expression. Using tissue immunofluorescence studies, we also report that the expression of MMP-9 is significantly decreased in activated HSCs in fibrotic tissues associated with hepatocellular carcinoma. This suggests the presence of a mechanical network that allows HSCs to maintain a fibrotic ECM, with external rigidity providing feedback which affects MMP-9 and TIMP-1 secretion, which may become dysregulated in fibrosis.